The significance of employing competitive intelligence at selected South African higher education institutions.: HEIs, ICT, CI - Mogale, R. J.; Mkhomazi, S.S; Iyamu, T. (South African Journal of Higher Education, 2025)
For many years, Higher Education Institutions (HEIs) are experiencing changes in information and communication technology (ICT). Their role as intermediaries is being transformed from intermediaries to enablers due to the changes in information sources, management practices, and institutional cultures (Abolarinwa and Yaya 2015). This research sought to investigate the significance of employing Competitive Intelligence (CI) at selected South African higher education institutions. A survey design was used as a quantitative research method, and data was obtained using structured questionnaires. The results show that employing Competitive Intelligence (CI) can contribute significantly to the effective functioning of HEIs. The study contends that this can only be accomplished by identifying future opportunities and threats of CI while generating potential solutions.